Music in Grahamstown, 1880-1900 - Sparrow, Marion Janet (Rhodes University, Faculty of Humanities, Department of Music, 1978)
From Introduction: The previous thesis on the study of music in Grahamstown took the development to the point in history which marked the end of the Kaffir Wars on the Eastern Frontier. From 1880 - 1900, the Military Tradition of Grahamstown remained a strong factor in the daily life of the growing community. During the first decade of this thesis, there were years of retrenching and depression and the rural community, who supported many of the musical concerts, were also hard hit by drought and rinderpest. These problems are noticeable during the course of many of the chapters. The difficulties were overcome. The community grew and new schools were established and the effects of the First City Volunteers being away on minor War efforts, followed by the commencement of the Anglo-Boer War, were only temporarily felt in the musical life of the City. There must be to some extent duplication of information already submitted in an earlier thesis on Church Music. Chapter II - on Music in the Churches - is indispensable, as it reveals much of the heart and soul of the community, and without it the overall picture of the development of music in all spheres, would lose its true balance. It has been impossible to trace all the composers represented on the programmes, particularly those of all the glees and popular songs of the day. In some cases possible composers may perhaps have been suggested. There are obvious misprints which have been hinted at in footnotes. The primary source of information for this thesis has been "The Journal". As virtually all the material has been taken from that source and almost every footnote would have read Ibid . .. , I have dispensed with the abbreviation and merely given the date. Where the source of information changed, this was indicated. Throughout I have adhered to the facts and my deductions and suppositions have been reduced to a minimum .
Keywords: Music -- South Africa -- Grahamstown -- History; Music -- South Africa -- Eastern Cape -- History